REFLEKSYJNOŚĆ W ŚWIETLE TEKSTÓW EUROPEJSKIEGO SYSTEMU OPISU KSZTAŁCENIA JĘZYKOWEGO - Janowska, Iwona (Neofilolog, 2019)
The Common European Framework of Reference for Languages is a document characterized by a high level of generality, addressed to a wide range of readers. The conceptual paradigm included in the document could constitute the basis for a new trend in language didactics; however, a lot of further work and research should be carried out for the new approach to achieve the status of independent and efficient methodology. The first prerequisite for introducing necessary modifications is a reflexive approach to the recommendations of CEFR, especially those which are methodological in character. The lack of any rules or procedures showing how to facilitate the achievement of learning objectives is the most frequent objection made against the CEFR. The focus on what has to be taught should go along with how to teach and why. Reflexivity which occupies a marginal position in the CEFR has to become a priority for its users if the methodology outlined there is to constitute the new era in language didactics.